2017
DOI: 10.2174/1874312901711010136
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Puerto Ricans with Rheumatoid Arthritis (RA) Receiving Early Treatment with Disease-Modifying Anti-Rheumatic Drugs using the American College of Rheumatology Definition of Early RA

Abstract: Background:Early treatment of rheumatoid arthritis (RA) results in better long-term outcomes. However, the optimal therapeutic window has not been clearly established.Objective:To determine the clinical outcome of Puerto Ricans with RA receiving early treatment with conventional and/or biologic disease-modifying anti-rheumatic drugs (DMARDs) based on the American College of Rheumatology (ACR) definition of early RA.Methods:A cross-sectional study was performed in a cohort of Puerto Ricans with RA. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies have reported worse outcomes associated with late initiation of RA [10,24,29,30]. Fewer studies, though, have specifically investigated the effects of late assessment by a specialist on RA long-term management outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported worse outcomes associated with late initiation of RA [10,24,29,30]. Fewer studies, though, have specifically investigated the effects of late assessment by a specialist on RA long-term management outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided evidence of disparities in RA treatment in the Puerto Rican population [ 9 , 10 ]. A cross-sectional study of Puerto Ricans with RA looked at disparities between those receiving their healthcare in a managed care system ( n = 67) and non-indigent patients treated in fee-for-service settings ( n = 147) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although arthritis is one of the most prevalent health conditions in Puerto Rico [8], few studies have been conducted in Puerto Rican or Hispanic populations specifically [9][10][11]. Studies in the broader US population have identified some racial and ethnic disparities, reporting higher levels of disease activity and worse functional status in Hispanic patients compared with white patients, although it is not clear why this is the case [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 120 126 In rheumatology, this concept has now been extensively explored in rheumatoid arthritis since 2010, 127 – 129 with disease-modification outcomes to use clearly defined by the OMERACT consensus, 130 132 allowing the achievement of numerous disease-modification trials demonstrating the effectiveness of early therapy to reduce or at least stabilize the risk of undesirable sequelae for up to 20 years. 133 138 …”
Section: The Burning Need For Disease-modification Trialsmentioning
confidence: 99%